Copper and sulphur co-doped titanium oxide nanoparticles with enhanced catalytic and photocatalytic properties. Issue 19 (21st August 2020) - Ortiz-Bustos, Josefa; Gómez-Ruiz, Santiago; Mazarío, Jaime; Domine, Marcelo E.; del Hierro, Isabel; Pérez, Yolanda
Abstract : Copper and sulphur co-doped titanium oxide nanoparticles have been prepared by the sol–gel method to develop versatile catalysts exhibiting enhanced catalytic and photocatalytic properties. Abstract : Copper and sulphur co-doped titanium oxide nanoparticles have been prepared by the sol–gel method to develop versatile catalysts exhibiting enhanced catalytic and photocatalytic properties. Structural, morphological, chemical composition, and optical characterizations of the synthesized titanium oxide nanoparticles have been carried out in order to study the effect of incorporating copper and sulphur on the catalytic and photocatalytic activities of TiO2 nanoparticles. Optimal incorporation of copper and sulphur to the titanium dioxide nanoparticles promotes the photocatalytic degradation of ciprofloxacin in water under irradiation of UV or visible light. Complete degradation of ciprofloxacin was achieved after 120 min with the 0.4% Cu–0.5% S–TiO2 photocatalyst using UV and in 90 min applying visible light. Cu–S–TiO2 nanoparticles also exhibit high activity (94–98% conversion) and excellent recyclability (with no loss of activity after 14 runs) in selective oxidation of thioanisole using H2 O2 as an oxidant.